AKUN MEDIA SOSIAL X WALI KOTA GIBRAN RAKABUMING SEBAGAI MEDIA KOMUNIKASI PENGADUAN MASYARAKAT: (Studi Kasus Tanggapan Masyarakat Kota Surakarta Sebagai Followers Akun X @gibran_tweet Dalam Merespon Pengaduan Masyarakat) - Devinka, Tri Vena; Riyanto, Buddy; Maserona, Lukas (Solidaritas, 2024)
Research Objective: To understand the responses of the people of Surakarta City, who are followers of the social media account X @gibran_tweet, regarding the speed of response to public complaints by the City of Surakarta. Research Methodology: This study is descriptive in nature with qualitative analysis. Data collection was conducted through interviews with followers of the Mayor of Surakarta, Gibran Rakabuming's account, @gibran_tweet. Theoretical Framework: This research incorporates several communication and social theories. Positive responses occur when the public's expectations and needs are met through quick and relevant responses, in line with two-way communication theory and uses and gratifications theory. Conversely, negative responses arise when public expectations are not met or the response is perceived as not serious, consistent with expectancy-valence theory and social influence theory. Research Findings: The findings indicate that two-way communication is present, and effective communication occurs when there is reciprocal interaction between the message sender from the @gibran_tweet account and the recipients, who are the followers representing the Surakarta community. Two indicators of response were identified: positive responses emerge when the public's expectations and needs are met through quick and relevant responses, while negative responses arise when expectations are unmet or the response is perceived as not serious. This explains the dynamics of interaction between the Mayor of Surakarta and the people of Surakarta through the social media platform X.